Housing Services, Homelessness, Transportation, and Well-being. (11th November 2018) - Courtin, E; Reinhard, E; Avendano, M
Abstract: Housing quality has a positive impact on older people's physical health. However, few studies have examined how specific national-level policies to improve the quality of housing for older people influence their mental health. The Winter Fuel Payment (WFP) is a universal, unconditional cash transfer ranging from £200 to £300. The policy was introduced in 1997 to fight excess winter mortality in old age by providing people aged 60 and over financial support towards the cost of fuel during winter months. Over 12 million people received the benefit in 2017. This paper uses six waves of the English Longitudinal Study of Ageing (ELSA – 2002 to 2015, N=17, 235) to examine the mental health effect of the subsidy. Applying individual fixed-effects models, we show that the WFP subsidy leads to a significant reduction in depressive symptoms among older people in the UK. In particular, becoming eligible to WFP is associated with a significant decrease in depressive symptoms levels (beta = -0.07; 95% CI: -0.12, -0.02). Our findings indicate that policies providing financial support to older people to maintain their housing quality have the potential to improve mental health.